Synthesis and characterization of Co/SBA-15 catalysts for Fischer-Tropsch synthesis - Anas, Mohd Naim (2012)
Fischer-Tropsch synthesis(FTS)is one of the most promising ways for the conversion of syngas to hydrocarbon products. Supported cobalt is the preferred catalyst for FTS due to its high selectivity to heavy hydrocarbons,low activity for water-gas-shift reaction and comparatively low price.Cobalt loaded SBA-15 catalysts were prepared by two different techniques including wetness impregnation and direct-synthesis methods.The characterization of the synthesized samples was done by X-ray diffraction (XRD),scanning electron microscopy(SEM)and N2 adsorption-desorption,.XRD measurements showed that the calcined cobalt catalyst did not modify the structure of SBA-15,proving that Co was present under the form of Co3O4 in the catalyst.The hexagonal structure of pores of SBA-15 was confirmed by SEM images for all samples.BET surface area showed that Co/SBA-15 catalyst prepared by direct synthesis method was produced high surface area and pore volume compared prepared by wetness impregnation method.